A Case Study: Exploring the Patterns and Functions of Mandarin-English-code-switching in Malaysian ACCA Classroom - Qi, Xinyi (Transactions on Social Science, Education and Humanities Research, 2024)
In Malaysia, due to the complexity of the population composition, students may possess diverse linguistic and cultural capitals, potentially resulting in a lack of a shared first language among both the teacher and their classmates. Although there are a considerable number of studies exploring Mandarin-English-code-switching practices in education, few studies have investigated its patterns and functions in Malaysia ACCA classroom contexts. This study conducts qualitative research on ACCA lessons at a public online Malaysian training center in the higher education phase, including observation and a case study by discourse analysis and multimodal conversation analysis, to explore what are the typical code-switching patterns in this education setting and how the Mandarin-medium instruction teacher mobilizes multiple resources to ensure knowledge accessibility and cater for more students in the classroom. Findings indicate that intra-sentential code-switching and situational code-switching are prominent from the perspective of speaking styles and sociolinguistics, and code-switching practices, occurring as an intentional teaching strategy, contribute to inclusive education, by facilitating more students to comprehend unfamiliar concepts more effectively and fostering better communication and engagement in learning.